Avaliação morfométrica das papilas ruminais de bovinos e bubalinos alimentados com dieta de alto grão - LIMA, Vivian Cristian de Freitas (Universidade Federal do Oeste do Pará, 2024)
The aim of the present work was to evaluate the influence of high grain diet on ruminal papilla morphometry of cattle and buffaloes. The study was conducted in the premises of the rural union of Santarém-PA. Twelve animals were used to carry out the experiment: six uncastrated buffalo and six uncastrated bovine cattle where they were allocated in individual pens and fed in total confinement, with initial body weight of approximately (271 and 291Kg) for cattle and (305 and 337kg) for buffaloes. The animals were blocked according to weight in a 2x2 factorial arrangement, comparing animal species (bovine and buffalo) and within each species two diets were compared. Animals were distributed evenly, using body weight at random in the following experimental diets, high-grain diet - GMI: 85% whole corn grain and 15% Engordin 38® kernel; GMM: 70% concentrated mixture, 90% ground corn grain and 10% Engordin 10® core, and corn silage. The confinement lasted 84 days, being 14 days of adaptation and 70 days of data collection. The GMM diet showed significant results (P <0.05) for the variables number of papillae (67 ± 4), area (0.14 ± 0.09), height (0.69 ± 0.17), width (0.22 ± 0.05) and absorptive area (16.25 ± 0.42) in relation to GMI diet for cattle. The results for buffalo were higher for GMM-fed animals and this difference is similar to that found for cattle. Regarding the height of the papillae there was no significant result (P> 0.05) when compared to GMI diets. The obtained data demonstrated that the nutritional plan affected the papillary morphometric data and absorption area. It was concluded that the GMM diet had better performance for papilla growth and development in relation to the GMI diet, thus increasing the nutrient absorption area.